Future sustainability of Kulliyyah of Education, International Islamic University Malaysia: The Way Forward - Mohd Ali, Hairuddin (2017)
The aim of this paper is to share what are the sustainability factors for the Kulliyyah of Education, International Islamic University Malaysia. It is a conceptual type of paper based on the actual planning of the kulliyyah for future sustainability of the IIUM in general and KoED in particular. The deliberation will be based on the ten shifts as stated in Malaysian Higher Education Blueprint (2015-2025). These ten shifts are then laid down and matched with IIUM’s strategic planning model for better future. The author also tried to share what the KoED has achieved so far based on the implementation of the organizational planning, Quality Assurance and Balanced Scorecard.